Periendoscopic management of direct oral anticoagulants: a prospective cohort study. Issue 6 (31st July 2018) - Radaelli, Franco; Fuccio, Lorenzo; Paggi, Silvia; Hassan, Cesare; Repici, Alessandro; Rondonotti, Emanuele; Semeraro, Rossella; Di Leo, Milena; Anderloni, Andrea; Amato, Arnaldo; Trovato, Cristina; Bravi, Ivana; et al.
Abstract : Objective: To assess the frequency of adverse events associated with periendoscopic management of direct oral anticoagulants (DOACs) in patients undergoing elective GI endoscopy and the efficacy and safety of the British Society of Gastroenterology (BSG) and European Society of Gastrointestinal Endoscopy (ESGE) recommendations (NCT 02734316). Design: Consecutive patients on DOACs scheduled for elective GI endoscopy were prospectively included. The timing of DOAC interruption and resumption before and after the procedures were recorded, along with clinical and procedural data. Procedures were stratified into low-risk and high-risk for GI-related bleeding, and patients into low-risk and high-risk for thromboembolic events. Patients were followed-up for 30 days for major and clinically relevant non-major bleeding events (CRNMB), arterial and venous thromboembolism and death. Results: Of 529 patients, 38% and 62% underwent high-risk and low-risk procedures, respectively. There were 45 (8.5%; 95% CI 6.3% to 11.2%) major or CRNMB events and 2 (0.4%; 95% CI 0% to 1.4%) thromboembolic events (transient ischaemic attacks). Overall, the incidence of bleeding events was 1.8% (95% CI 0.7% to 4%) and 19.3% (95% CI 14.1% to 25.4%) in low-risk and high-risk procedures, respectively. For high-risk procedures, the incidence of intraprocedural bleeding was similar in patients who interrupted anticoagulation according to BSG/ESGE guidelines or earlier (10.3%vs10.8%, p=0.99), with a trend for a lower risk as compared with those who stopped anticoagulation later (10.3%vs25%, p=0.07). The incidence of delayed bleeding appeared similar in patients who resumed anticoagulation according to BSG/ESGE guidelines or later (6.6%vs7.7%, p=0.76), but it tended to increase when DOAC was resumed earlier (14.4%vs6.6%, p=0.27). The risk of delayed major bleeding was significantly higher in patients receiving heparin bridging than in non-bridged ones (26.6%vs5.9%, p=0.017). Conclusion: High-risk procedures in patients on DOACs are associated with a substantial risk of bleeding, further increased by heparin bridging. Adoption of the BSG/ESGE guidelines in periendoscopic management of DOACs seems to result in a favourable benefit/risk ratio. Trial registration number: NCT 02734316 ; Pre-results.